Overlapping the Tryptophan Catabolite (TRYCAT) and Melatoninergic Pathways in Alzheimer's Disease - Maes, Michael; Anderson, George (Current Pharmaceutical Design, 2016)
Activation of the trptophan catabolite (TRYCAT) pathways by oxidative and nitrosative stress and proinflammatory cytokine-driven indoleamine 2,3-dioxygenase (IDO) and tryptophan 2,3-dioxygenase (TDO) leads to the synthesis of a number of neuroregulatory TRYCATs, such as kynurenic acid and quinolinic acid. Such TRYCATs have significant impacts on neuronal functioning and survival contributing to the changes seen in Alzheimer's disease (AD), including in its association with depression as well as alterations in the reactivity of immune and glia cells. By decreasing the availability of tryptophan for serotonin synthesis, such IDO and TDO-driven TRYCATs, also decrease the availability of serotonin for N-acetylserotonin (NAS) and melatonin synthesis. The loss of NAS and melatonin has significant consequences for the etiology, course and treatment of AD, including via interactions with altered TRYCATs, but also by changing the levels of trophic support and modulating the patterning of immune activity. In this review, we look at how such interactions of the TRYCAT and melatoninergic pathways link a plethora of previously diffuse data in AD as well as the treatment implications and future research directions that such data would suggest.
Keywords: melatonin